Performance differentials within geographic clusters - McCann, Brian T.; Folta, Timothy B. (Journal of Business Venturing, 2011)
Increasing evidence indicates that firms benefit from a location in a geographic cluster of similar firms. The literature is nearly silent, however, on whether agglomeration economies accrue symmetrically across clustered firms. Drawing from the knowledge-based view, we investigate which firms benefit most from agglomeration and discuss how the implications for entrepreneurs are significant if some firms benefit more from geographic agglomeration than others. We investigate three particular firm attributes that may accentuate or mitigate benefits tied to participation in a cluster. We test our hypotheses on a sample of biotechnology firms and find strong evidence that firms benefit asymmetrically. Younger firms and firms with higher knowledge stocks benefit more from agglomeration.